Islam merentasi bidang - A. Monir Yaacob (Abdul Monir Yaacob), Dato' (Kuala Lumpur : Techknowlogic Trading Sdn. Bhd., 2013)
Essays on Islamic doctrines and it practice in various fields; collected articles.
Includes bibliographical references (pages 285-287) and index.
In Malay.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Islam -- Study and teaching; Islam; Islam -- Doctrines